A duplication/deficient X chromosome in a girl with mental retardation and dysmorphic features. - Barnes, I C (1988)
A structurally abnormal X chromosome was found in a nine year old girl with mild mental retardation and dysmorphic features. Subsequent clinical examination at 18 years of age showed tall stature and gonadal dysgenesis. Re-examination of her karyotype using a variety of banding techniques on prometaphase chromosomes allowed the identification of the abnormal chromosome as a duplication/deficient X chromosome, 46,Xder X(pter----q28::p11.2----pter). The clinical features are discussed in terms of karyotype/phenotype correlation.